Signal analysis with Zetasizer on the effect of Poly (Ethylene Glycol) (PEG) to stabilize and unify colloidal gold nanoparticles - G., F. Chin; Misni, Misran, Dr.; P, Y. Tang; P., F. Lee (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/